Strategia hands-on activity w kreowaniu geoproduktów w kontekście edukacji, interpretacji i promocji geodziedzictwa na Roztoczu (środkowowschodnia Polska) - Teresa Brzezińska-Wójcik (Ekonomiczne Problemy Turystyki, 2015)
The application of the hands-on activity strategy is essential in the interpretation of geological and geomorphological heritage in the context of changing expectations of tourists, as well as in relation to the necessity to create unconventional products using traditional resources in an innovative way. The objective of the paper is to present examples of good practices throughout the world (geoparks: Arouca and Naturtejo in Portugal, Vulkaneifel in Germany, Ţara Haţegului Geoparcul Dinozaurilor in Romania, Gea Norvegica in Norway, Araripe in Brasil and Réserve Géologique de Haute-Province in France) in the scope of use of simple geoproducts employing the hands-on activity strategy for education, interpretation, and promotion of geoheritage. Based on the field cataloguing of geological and geomorphological resources, the paper presents a hypothetical model of possible application of the hands-on activity strategy in the preparation of simple geoproducts in Roztocze.